Studie av behandlingseffekt ved Raskere Tilbake-tilbudet hos Betania Malvik 2009-2015 - Bjørnerud, Kim Andre; Tvedt, Morten Andreas (Nordisk tidsskrift for helseforskning, 2017)
<span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"><span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: NO-BOK; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Enhet for Helse og Arbeidsliv provides treatment services for patients with mild mental disorders within Raskere Tilbake. <span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The purpose of this study is to evaluate the effect of the treatment. The study includes patients with mild mental disorders who have completed their treatment during the period 2009 to March 2015. The SCL 90-R was administered before arrival and at the end of treatment. Degree of return to work was measured as sick leave rate by the end of treatment and patients were contacted telephonically after 3, 6, 12 and 24 months for questions about sickness benefit. There has been a significant reduction in symptom pressure measured before and after treatment using SCL 90-R both on the global symptom index, and the various sub-scales. The proportion of total or partial return to work at the end of treatment was 76% (n = 148), 89% (n = 79) after three months, 93% (n = 67) after six months, 94% (n = 50) after 12 months, and 100% were fully or partially back to work after 24 months (n = 7).